Voltage Oriented Decoupled Control Scheme for DFIG’s Grid Side Converter - S.A Kamran; Javier Muñoz (Universitas Ahmad Dahlan, 2018)
This paper proposes a novel voltage oriented decoupled control scheme for the DFIG’s Grid Side Converter (GSC) of a 2.3Mw, 690V, 50Hz, 6 pole doubly-fed induction generator (DFIG) based wind generation system. For Rotor Side Converter (RSC), slip and constant V/Hz control scheme along with a feedback control via PWM is selected but not explained in this paper.Based on the per-phase steady state equivalent circuit model of a DFIG, relationship between stator and rotor voltages is developed. Voltage oriented decoupled control scheme for GSC is designed in such a way that it can keep the dc link voltage constant by regulating grid reactive power when required. The space vector modulation (SVM) algorithm is explained breifly and implemented for the two-level GSC. MATLAB/SIMULINK (R2015a) software validates the proposed control scheme for GSC.